ANALISIS PENOLAKAN PARTAI KEADILAN SEJAHTERA TERHADAP PEMINDAHAN IBU KOTA NEGARA - Astin Julia Rosa (2023)
Moving the nation's capital is not something new, because Indonesia has been planning to move the nation's capital since the era of President Soeharto's administration until finally in the era of Joko Widodo's administration the plan was realized. The research in this thesis examines the rejection conveyed by PKS as an opposition party during the Joko Widodo administration towards the agenda of moving the country's capital to East Kalimantan Province. This research also aims to analyze how the role of the Prosperous Justice Party as part of the opposition party regarding the policies of Law Number 3 of 2022 concerning the National Capital has made the Prosperous Justice Party a balancer of political power and social control in parliament. This thesis uses qualitative research methods, by collecting data through direct interviews with sources and making observations. In this research, the research subjects studied were council members from the Prosperous Justice Party faction, Walhi NGO, as well as local communities who live at the IKN Nusantara construction site. The theory used in this research is the opposition theory presented by Robert Dahl and the zero sum game concept by Erika S. Olson. The research results show that the rejection by the Prosperous Justice Party faction of the relocation of the country's capital has strengthened PKS's position as the only opposition party and a balancer of political power in the Joko Widodo and Ma'ruf Amin administration era in the post-reformation era. Apart from that, the social control function in the IKN transfer policy, PKS revealed various reasons for rejection, one of which was regarding the very large budget for the IKN development process which reached 5 stages until 2045. Apart from that, PKS assessed that the Rights of Indigenous Peoples were not found in The IKN Bill until it has been passed into Law Number 3 of 2022 concerning the National Capital. Apart from that, the function of balancing political power that PKS has has not been implemented stably because the low number of political parties that are part of the opposition has made PKS experience a lack of votes in every vote on a policy, especially on the policy of moving the country's capital to IKN Nusantara.